Teaching Ethics: Between Indoctrination, Frustration, and Self-Censorship? - Klampfer, Friderik (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
In this paper, I discuss some of the dilemmas that teachers face when teaching ethics. I advocate for a design and implementation of ethics classes that best equip students for independent and reflective moral judgment and/or deepen their moral understanding, even if it turns out that potential progress in the knowledge, skills, and abilities that form the basis for these does not automatically translate into morally improved decisions and actions. I insist that ethics classes should be clearly distinguished from traditionally understood ethical or moral education, which primarily aims for lasting changes in behavior or behavioral dispositions. I find that curricula for subjects that mention ethics in their titles and promise to address selected ethical issues and topics contain elements of both training in moral judgment and moral education. However, especially at the primary and secondary education levels, the latter, unfortunately, tends to overshadow the former.